Teknik Penerjemahan Amplifikasi Dalam Takarir Film “Gintama Live Action” Karya Hideaki Sorachi - Adriansyah, Marcellino; Mulya, Komara (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
This study aims to determine the form and function of the amplification translation technique in the subtitle of the film "Gintama Live Action" by Hideaki Sorachi. The theory used is the theory of translation techniques from Molina & Albir (2002:510) where the addition of this technique is by revealing the details of the message explicitly or paraphrasing an implicit information from Source Language into Target Language. The method used for this research is descriptive qualitative method and observe with note-taking technique because this study uses film objects as a place to find data related to research. From the results of this study, it is known that there is an amplification translation technique with an explicit form that serves to add meaning to ambiguous words. Then, the form of footnotes is to provide information in the form of references to make it easier for the audience to understand the meaning contained in the conversation, both historically and culturally. Descriptive form is to add the shape of the object or character being discussed. Last, paraphrase form is to explain the meaning of a sentence that has no lexical equivalent in the target language.